2011
DOI: 10.1007/s10409-011-0474-4
|View full text |Cite
|
Sign up to set email alerts
|

Flow structures of gaseous jets injected into water for underwater propulsion

Abstract: Gaseous jets injected into water are typically found in underwater propulsion, and the flow is essentially unsteady and turbulent. Additionally, the high water-to-gas density ratio can result in complicated flow structures; hence measuring the flow structures numerically and experimentally remains a challenge. To investigate the performance of the underwater propulsion, this paper uses detailed NavierStokes flow computations to elucidate the gas-water interactions under the framework of the volume of fluid (VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…All of the simulations were modeled using the commercial CFD (Computational Fluid Dynamics) code, ANSYS-Fluent. The VOF multi-phase model is used to track the change of gas-liquid interface, and this model has been validated in getting the fraction of gas in underwater gaseous jets [10,15,19]. The two-dimensional axisymmetric geometric model with the same size of water vessel is established for simulation, and the pressure-velocity coupling SIMPLE algorithm is used to solve the discrete equations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the simulations were modeled using the commercial CFD (Computational Fluid Dynamics) code, ANSYS-Fluent. The VOF multi-phase model is used to track the change of gas-liquid interface, and this model has been validated in getting the fraction of gas in underwater gaseous jets [10,15,19]. The two-dimensional axisymmetric geometric model with the same size of water vessel is established for simulation, and the pressure-velocity coupling SIMPLE algorithm is used to solve the discrete equations.…”
Section: Methodsmentioning
confidence: 99%
“…Loth et al [9] found that the same shock structures in the wake of a sonic jet underwater. Wang et al [10,11], Shi et al [12,13], and Tang et al [14,15] found that expansion, necking, and back-attack are fundamental phenomena in underwater gas jets. Tang et al [16,17] considered phase transitions and the buoyancy effect of gaseous jets for underwater propulsion systems through numerical simulation, and found that the thrust shows different orders of frequency attributed to the oscillation in wake.…”
Section: Introductionmentioning
confidence: 99%
“…A development of "Back-Attack phenomenon" in supersonic gaseous jets was made by Tang et al [Tang, 2011]. The converging-diverging Laval nozzles are used in Tang's article.…”
Section: Unsteadiness Of Jet Development Processes and Flow Structuresmentioning
confidence: 99%
“…Observations of Dai et al [Dai, 2006] have shown that the injection process of high-speed gaseous jets in still water can induce large pressure pulsations upstream of the nozzle exit, and that the shock-cell structures in the over-and under-expanded jets can lead to strong changes in the hydrodynamic pressure. Shi et al [Shi, 2010] have shown that the injection of supersonic gaseous jets into water causes large flow oscillation, which can be related to shock waves reflecting in the gas phase and, complementarily, Tang et al [2011] has observed the back-attack phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation